Mesenchymal Stem Cells: A Potential Therapeutic Approach for Amyotrophic Lateral Sclerosis? - Agnese Gugliandolo; Placido Bramanti; Emanuela Mazzon (Stem Cells International)
Amyotrophic lateral sclerosis (ALS) is a neurodegenerative disease characterized by the degeneration of both upper and lower motor neurons. Patients show both motor and extra-motor symptoms. A cure is not available at this time, and the disease leads to death within 3–5 years, mainly due to respiratory failure. Stem cell therapy is arising as a new promising approach for the treatment of neurodegenerative disorders. In particular, mesenchymal stem cells (MSCs) seem the most suitable type of stem cells, thanks to their demonstrated beneficial effects in different experimental models, to the easy availability, and to the lack of ethical problems. In this review, we focused on the studies involving ALS rodent models and clinical trials in order to understand the potential beneficial effects of MSC transplantation. In different ALS rodent models, the administration of MSCs induced a delay in disease progression and at least a partial recovery of the motor function. In addition, clinical trials evidenced the feasibility and safety of MSC transplantation in ALS patients, given that no major adverse events were recorded. However, only partial improvements were shown. For this reason, more studies and trials are needed to clarify the real effectiveness of MSC-based therapy in ALS.